Information technology in university‐level mathematics teaching and learning: a mathematician’s point of view - Borovik , Alexandre (Research in Learning Technology, 2011)
Although mathematicians frequently use specialist software in direct teaching ofmathematics, as a means of delivery e-learning technologies have so far been lesswidely used. We (mathematicians) insist that teaching methods should be subjectspecificand content-driven, not delivery-driven. We oppose generic approaches toteaching, including excessively generalist, content-free, one-size-fits-allpromotion of information and communications technology. This stance is fullyexpressed, for example, in the recent Teaching Position Statement from the LondonMathematical Society (2010) and is supported by a recent report from the NationalUnion of Students (2010, 5): “Not every area of study needed or was compatiblewith e-learning, and so to assume it would grant blanket advantages was notaccurate”. This paper is an attempt to explain mathematicians’ selectivity in use ofinformation and communications technology and its guiding principles. The paperis addressed to our non-mathematician colleagues and is not intended to be a surveyof the existing software and courseware for mathematics teaching – the corpus ofexisting solutions is enormous and its discussion inevitably involves hardcoremathematics. 10.1080/09687769.2010.548504